Congenital Lumbar Hernia: A 15-Year Experience at a Single Tertiary Centre - K. N. Rattan; Arushi Agarwal; Ankur Dhiman; Ananta Rattan (International Journal of Pediatrics)
Aim. Congenital lumbar hernia is an uncommon anomaly with only few cases reported in the English literature. This study was done to study the incidence, age at presentation, sex, associated anomalies, surgical management, and postoperative morbidity and mortality of congenital lumbar hernia in pediatric patients. Methods. Retrospective analysis of all patients of CLH over a period of 15 years (January 2000 to December 2015) was analyzed. Results. A total of 14 patients were encountered in this series. All presented within first 2 years of age. 12 were males and 2 were females. All of them presented with swelling in lumbar region. 13 were unilateral and 1 was bilateral. Left sided hernia was observed in 2 cases only. Lumbocostovertebral syndrome was found in all the patients in addition to other rare anomalies. All cases were managed with open surgical repair. Wound infection was seen in 2 cases. There was no mortality in our series. Conclusion. CLH is very rare among hernias. Surgery should be carried out within 1 year of age. For a defect of <5 cm, primary repair is done. For a defect of >5 cm, meshplasty should be considered. Prognosis is excellent.